Participation of muallaf in the mosque activities in enhancing Islamic tolerance - Razaleigh Muhamat @ Kawangit; Anuar Puteh; Nur A’thiroh Masya’il Tan Abdullah (Universiti Kebangsaan Malaysia, 2013)
In the development of Muslim community, mosque is considered a nerve centre. Though varying in dimensions and structures, the mosque becomes a place of worship five times a day as well as a symbol for the diffusion of „truly‟ Islamic knowledge. Since the approach of Islamic tolerance values was introduced by the Malaysian government in 2004, the mosques throughout the country have actively promoted the new ways of improving the life of Muslims, especially among Muallaf. This study is an attempt to examine the administration and activities of the mosques in supporting the ideas of Islamic tolerance values. Friday‟s khutbah (sermons), religious preaching, forums as well as the celebration of various events in the Islamic calendar will be analysed in order to illustrate how the new understanding of Islam is being promoted to the Muallaf. This paper argues that the mosque, where the believers assemble for prayers as well as for the spiritual upliftment, is the respectable premise that should be utilised extensively for the changing of Muslim minds towards this worldly life.